Scientific process skills: Preliminary study towards senior high school student in Palembang - Tri Eka Andini; Saleh Hidayat; Etty Nurmala Fadillah; Tutut Indria Permana (University of Muhammadiyah Malang, 2018)
The 21st-century challenges require the next generations to have various skills to deal with, including scientific process skills. This study aimed to describe the scientific process skills of the senior high school student in Palembang in term of ecology subject. This descriptive quantitative research observed 231 respondents of the tenth-grade student from two different sub-districts in Palembang, Gandus and West Ilir. The student’s scientific process skills were measured using the test instrument and interview. The results showed that there were various outcomes for each indicator in Gandus i.e. 68.87% (observing), 75.00% (grouping), 54.81% (interpreting), 73.08% (predicting), 52.56% (formulating a hypothesis), 49.04% (planning an experiment), and 43.59% (communicating). Meanwhile in West Ilir the outcomes for students’ scientific process skills were 69.48% (observing), 66.34% (grouping), 56.65% (interpreting), 64.04% (predicting), 59.64% (formulating a hypothesis), 47.85% (planning an experiment), and 41.39% (communicating). It can be concluded that the students’ scientific process skills in Palembang were categorized as the medium. Hence, strategies to promote students’ scientific process skills in biology class still need to be improved especially in ecology learning.